Konsep Pembagian Harta Bersama Akibat Perceraian dalam Perkawinan Siri - Nourma Dewi; Raharno . (Jurnal Supremasi, 2019)
Marriage registration is still limited to the existence recognized by the state is not the main condition of the legality of the marriage. In practice, many sirri marriages occur in the community and such marriages sometimes do not achieve the goal of a happy and everlasting marriage that causes divorce. The problem that needs to be examined is the divorce from the sirri marriage how the concept of division of shared assets. This research uses normative research methods. KHI regulates the determination of marriage by the court or itsbat marriage. After the stipulation results in the enactment of the law of joint sharing as regulated in Article 37 of the UUP and Article 97 of KHI.